Cu2O/g-C3N4 nanocomposites: an insight into the band structure tuning and catalytic efficiencies. Issue 45 (8th November 2016) - Mitra, Anuradha; Howli, Promita; Sen, Dipayan; Das, Biswajit; Chattopadhyay, Kalyan Kumar
Abstract : Cu2 O/ g -C3 N4 nanocomposites with tuned optical properties and the highest catalytic efficacy in the chemical decomposition of methyl orange without any light illumination. Abstract : We demonstrate an easy and scalable room-temperature synthesis of Cu2 O nanoparticle incorporated graphitic carbon nitride composites without the aid of any inert atmosphere. First principles calculations based upon density functional theory, in addition to the experimental validations, have been employed to investigate the electronic and optical properties of the nanocomposites. An insight into the band structure tunability, phase stabilisation and the dependancy of the catalytic properties of the nanocomposites upon the amount of Cu loading, in the form of Cu oxides, have been provided in this work.